THE EFFECTS OF ICT-BASED LEARNING ON STUDENTS’ VOCABULARY MASTERY IN JUNIOR HIGH SCHOOLS IN BANDUNG - Hussain, Zakir (UPI Press, 2018)
ICT plays a vital role in English language learning since it boosts motivation (Schoepp Erogul, 2001), learners’ autonomy (Tri. et al., 2014) and learning skills (Galavis, 1998). This study aimed to examine the effects of ICT-based learning using wiki on learning of students’ vocabulary mastery at the junior high school. The design of the present study was quasi-experimental study. The population of the study was seventh graders of a junior high school in Bandung. Experimental group and control group comprised of 25 students each. The instruments of the study were a pre-test and a post-test of vocabulary mastery and an online learning platform called wiki. The data were analyzed by SPSS 16.0 for the windows. The findings revealed that there were significant differences at .05 level between experimental group and control group (df= 49, t= 2.02). Furthermore, recommendations are proposed for the teachers whose teaching philosophy is twisted with ICT-based learning. For instance, they should provide an interesting topic on the wiki, let them chat while working online, assign them working at home and well prepare the facilities used in the class before starting of the lesson.